Factors that influence food choices in secondary school canteens: a qualitative study of pupil and staff perspectives - Devine, Lauren D.; Gallagher, Alison M.; Briggs, Stephen; Hill, Alyson J. (Frontiers in Public Health, 2023)
Background Adolescence is recognised as a period of nutritional vulnerability, with evidence indicating that United Kingdom adolescents have suboptimal dietary intakes with many failing to meet dietary recommendations. Additionally, adolescence is a time of transition when they become more independent in their dietary choices and begin to develop their own sense of autonomy and are less reliant on their parent’s guidance, which is reported to lead to less favourable dietary behaviours. Reducing the prevalence of poor dietary intakes and the associated negative health consequences among this population is a public health priority and schools represent an important setting to promote positive dietary behaviours. The aim of this school-based study was to explore the factors and barriers which influence food choices within the school canteen and to identify feasible strategies to promote positive dietary behaviours within this setting. Methods Thirteen focus groups with 86 pupils in Year 8 (n = 37; aged 11–12 years) and Year 9 (n = 49; aged 12–13 years) in six secondary schools across Northern Ireland, United Kingdom were conducted. Additionally, one-to-one virtual interviews were conducted with 29 school staff [principals/vice-principals (n = 4); teachers (n = 17); and caterers (n = 7)] across 17 secondary schools and an Education Authority (EA) senior staff member (n = 1). Focus groups and interviews were audio-recorded, transcribed, and analysed following an inductive thematic approach. Results Using the ecological framework, multiple factors were identified which influenced pupils’ selection of food in the school canteen at the individual (e.g., time/convenience), social (e.g., peer influence), physical (e.g., food/beverage placement), and macro environment (e.g., food provision) level. Suggestions for improvement of food choices were also identified at each ecological level: individual (e.g., rewards), social (e.g., pupil-led initiatives), physical (e.g., labelling), and macro environment (e.g., whole-school approaches). Conclusion Low-cost and non-labour intensive practical strategies could be employed, including menu and labelling strategies, placement of foods, reviewing pricing policies and whole-school initiatives in developing future dietary interventions to positively enhance adolescents’ food choices in secondary schools.